Easy

Algebra Level 4

x + y + z = 0 x 2 + y 2 + z 2 = 6 x 3 + y 3 + z 3 = 6. x + y + z = 0\\x^2 + y^2 + z^2 = 6\\x^3 + y^3 + z^3 = -6. x 2016 + y 2016 + z 2016 = 2 B + C , x^{2016} + y^{2016} + z^{2016} = 2^B + C, where 0 C < 2 B 0 \leq C < 2^B and B B is a positive integer.

Find 2 + B + C 2 + B + C .


The answer is 2020.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Surya Sharma
Feb 14, 2016

Solve the three equations (x,y,z)=(1,1,-2) in any order Which is (1)^(2016)+(1)^(2016)+(-2)^(2016) =(-2)^(2016)+2 A=-2,B=2016 and C=2 Hence the answer is 2016 But the important thing to note here is that (-2)^(2016)=(2)^(2016) So A=±2 Hence 2020 can be another answer

Yes, answer can be both 2016 and 2020.

Archit Agrawal - 5 years, 4 months ago

Log in to reply

ans can be a 1014 too as a=4 b=1008 and c=2 and there are so many such possibilities though i got to understand that why it has been reported by multiple users and got to know the possible mistake but you should accept that it is wrongly stated.

aryan goyat - 5 years, 4 months ago

Log in to reply

Thanks. I have edited the problem for clarity. Those who answered 2020 and 1014 have been marked correct. The correct answer is now 2020.

In future, if you spot an error with the problem, please report it so that we can take the necessary action.

Calvin Lin Staff - 5 years, 3 months ago
Tom Engelsman
May 13, 2021

Let x 3 + y 3 + z 3 = ( x 2 + y 2 + z 2 ) + ( x + y + z ) ( x 3 + x 2 x ) + ( y 3 + y 2 y ) + ( z 3 + z 2 z ) = 0. x^3 + y^3 + z^3 = -(x^2+y^2+z^2) + (x+y+z) \Rightarrow (x^3+x^2-x) + (y^3+y^2-y) + (z^3+z^2-z) = 0. If we now add 3 -3 to both sides, we now obtain:

( x 3 + x 2 x 1 ) + ( y 3 + y 2 y 1 ) + ( z 3 + z 2 z 1 ) = 3 ; (x^3+x^2-x-1) + (y^3+y^2-y-1) + (z^3+z^2-z-1) = -3;

or [ x 2 ( x + 1 ) ( x + 1 ) ] + [ y 2 ( y + 1 ) ( y + 1 ) ] + [ z 2 ( z + 1 ) ( z + 1 ) ] = 3 ; [x^2(x+1)-(x+1)] + [y^2(y+1) - (y+1)] + [z^2(z+1)-(z+1)] = -3;

or ( x 2 1 ) ( x + 1 ) + ( y 2 1 ) ( y + 1 ) + ( z 2 1 ) ( z + 1 ) = 3 (x^2-1)(x+1) + (y^2-1)(y+1) + (z^2-1)(z+1) = -3 ;

or ( x 1 ) ( x + 1 ) 2 + ( y 1 ) ( y + 1 ) 2 + ( z 1 ) ( z + 1 ) 2 = 3 (x-1)(x+1)^2 + (y-1)(y+1)^2 + (z-1)(z+1)^2 = -3

which has triplet solutions ( x , y , z ) = ( 2 , 1 , 1 ) ; ( 1 , 2 , 1 ) ; ( 1 , 1 , 2 ) (x,y,z) = (-2,1,1); (1,-2,1); (1,1,-2) , and x 2016 + y 2016 + z 2016 = 2 + 2 2016 B = 2016 , C = 2 x^{2016} + y^{2016} + z^{2016} = 2 + 2^{2016} \Rightarrow B = 2016, C = 2 . Hence, 2 + B + C = 2 + 2016 + 2 = 2020 . 2 + B + C = 2+2016+2 = \boxed{2020}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...